Analysis of Democratic Leadership Style Impact on Employee Management Performance (Case Study of Bank Mega Syariah KCP Makassar Latimojong) - Ismail, Ismail; Pasaribu, Veta Lidya Delimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the implementation of democratic leadership style in Bank Mega Syariah KCP Makassar Latimojong and its impact on employee performance. This study utilizes qualitative methodology with data collection through participant observation and informant interviews. The results of the study show the benefits of the democratic leadership approach in Bank Mega Syariah KCP Makassar Latimojong. Employees feel increased involvement, motivation, and accountability for their work. Employees now feel appreciated and recognized by management, and their happiness and work productivity increase. Improving communication and openness, involving staff in strategic planning, developing participatory leadership skills, encouraging collaboration and teamwork, and implementing regular assessment and feedback are some of the ideas made to strengthen democratic leadership. This study emphasizes the importance of democratic leadership in fostering an inclusive and inspiring workplace and enabling staff to perform better.